Development and evaluation of two rapid lateral flow assays for on-site detection of African swine fever virus - Wang, Lihua; Kim, Juhun; Kang, Hyangju; Park, Hong-Je; Lee, Min-Jong; Hong, Sung-Hee; Seo, Chang-Won; Madera, Rachel; Li, Yuzhen; Craig, Aidan; Retallick, Jamie; Matias-Ferreyra, Franco; et al. (Frontiers in Microbiology, 2024)
Introduction: African swine fever (ASF) is a lethal and highly contagious transboundary animal disease with the potential for rapid international spread. In the absence of widely available and definitively proven vaccinesafe and effective vaccine, rapid and early detection is critical for ASF control. The quick and user-friendly lateral flow assay (LFA) can easily be performed by following simple instruction, and is ideal for on-site use. This study describes the development and validation of two LFAs for rapid detection of ASF virus (ASFV) in pig serum.The highly immunogenic antigens (p30 and p72) of ASFV Georgia 2007/1 (genotype II) were expressed in plants (Nicotiana benthamiana) and were used to immunize BALB/c mice to generate specific monoclonal antibodies (mAbs) against p30 and p72 proteins. These mAbs with the strongest binding ability to each protein were employed to develop p30_LFA and p72_LFA for detecting the respective ASFV antigens. The assays were first evaluated using a spike-in test by adding the purified p30 or p72 protein into serum sample from a healthy donor pig. Further validation of the tests was carried out using serum samples derived from experimental infected domestic pigs, field domestic pigs and feral pigs, and the results were compared with those of ASFV real-time PCR.Results: p30_LFA and p72_LFA showed no cross-reaction with common swine viruses and delivered visual results in 15 minutes. When testing with serially diluted proteins in swine serum samples, analytical sensitivity reached 10 ng/test for p30_LFA and 20 ng/test for p72_LFA. Using real-time PCR as a reference, both assays demonstrated high sensitivity (84.2180% for p30_LFA, 100% for p72_LFA) with experimentally ASFV infected pig sera. Specificity was 100% for both LFAs using a panel of PBS inoculated domestic pig sera. Excellent specificity also showed for field domestic pig sera (100% for p30_LFA, 93% for p72_LFA) and feral pig sera (100% for both LFAs).The results obtained in this study suggest that p30_LFA and p72_LFA hold promise as rapid, sensitive, user-friendly, and field-deployable diagnostic tools for ASF control, particularly in settings with limited laboratory resources.